Prevalence of hypertriglyceridemic waist and association with risk of type 2 diabetes mellitus: a meta‐analysis. Issue 4 (4th November 2015) - Ren, Yongcheng; Luo, Xinping; Wang, Chongjian; Yin, Lei; Pang, Chao; Feng, Tianping; Wang, Bingyuan; Zhang, Lu; Li, Linlin; Yang, Xiangyu; Zhang, Hongyan; Zhao, Jingzhi; et al.
Abstract: Introduction: A meta‐analysis of studies assessing the prevalence of hypertriglyceridemic waist and an association with risk of type 2 diabetes mellitus (T2DM). Materials and methods: PubMed, EMBASE, Web of Science, CNKI, CQVIP and Wanfang databases were searched for studies of the prevalence of hypertriglyceridemic waist or association with risk of T2DM. Reference lists of each original article were also searched. A random‐effects model was used to synthesize the combined prevalence and odds ratios. Publication bias and substantial heterogeneity were examined. Results: Twenty‐five eligible studies involving 93 194 participants (93 194 for prevalence and 34 199 for odds ratios): 17 articles of prevalence, and 8 of both prevalence and risk of T2DM. Prevalence of hypertriglyceridemic waist ranged from 4% to 47%, with pooled prevalence of 18% (95% CI 13–23%), overall: 18% (95% CI 13–23%) for men and 19% (95% CI 13–24%) for women. Odds ratios ranged from 2.8 to 9.6 for T2MD in overall, with pooled odds ratios of 4.18 (95% CI 3.55–4.92), overall: 3.55 (95% CI 2.93–4.31) for men and 4.18 (95% CI 3.43–5.09) for women. Discussion/conclusion: The prevalence of hypertriglyceridemic waist has reached an alarming level and is closely associated with increased risk of T2DM in the general population, particularly among women and among brown‐skinned men and women. Copyright © 2015 John Wiley & Sons, Ltd.